Klippel-Trenaunay Syndrome and Pregnancy - Tuğba Güngor Gündoğan; Y. Jacquemyn (Obstetrics and Gynecology International)
Klippel-Trenaunay syndrome is a rare congenital vascular disorder, and only few cases have been described in pregnancy. We describe two cases, in one patient without complications, the other patient developed postpartum deep venous thrombosis.